Adaptive medium access control protocol for dynamic medical traffic with quality of service provisioning in wireless body area network - Mohd Ali, Darmawaty; Wan Hassan, Wan Haszerila; Sarang, Sohail; M. Stojanović, Goran; Wan Muhamad, Wan Norsyafizan; Ya'acob, Norsuzila (Institute Of Electrical And Electronics Engineers Inc., 2024)
The performance of a Wireless Body Area Network (WBAN) depends on the Quality of Service (QoS) and energy efficiency. The traffic generated by WBAN is heterogeneous in nature, and consists of both periodic and emergency events. One crucial challenge in designing a WBAN Medium Access Control (MAC) protocol is guaranteeing high-reliability transmission while satisfying diverse QoS requirements. Therefore, this paper proposes a QoS-aware MAC protocol named the Adaptive MAC (ADT-MAC) that accommodates dynamic medical traffic by addressing emergency and periodic traffic requirements. ADTMAC utilizes a hybrid and adaptive superframe structure based on the IEEE 802.15.6 standard. Additionally, an M/M/1 queuing algorithm with a non-preemptive priority is modeled using SimEvents in MATLAB to validate the packet delay of the priority queues. The proposed ADT-MAC protocol is simulated using Castalia and OMNeT++ to evaluate its performance against state-of-the-art MAC protocols. Simulation findings reveal that ADT-MAC achieves lower packet delay, higher PDR, and increased network throughput while reducing energy consumption compared to its benchmarks. Furthermore, the result of packet delay from priority queues validates the accuracy of the proposed ADT-MAC and queueing algorithm. The two-fold simulation approach using Castalia and SimEvents demonstrated that the packet delay for each priority level remains below the 125 ms threshold set by the IEEE 802.15.6 specifications.